Intranasal Treatment of Acute Rhinosinusitis - Recommendations, Efficacy and Safety - Sadlik, Maria; Abod, Leila; Ilnicka, Natalia; Matyja, Daria; Zuziak, Patrycja (Journal of Education, Health and Sport, 2023)
Introduction and purpose: Acute rhinosinusitis is a common condition worldwide, usually caused by respiratory viruses. Nasal epithelium is their primary point of entry and an active responder to the infection. Therefore, it seems reasonable for the treatment approach to include locally applied drugs. Our purpose is to bring forward up-to-date recommendations of intranasal treatment options for acute rhinosinusitis, and assess their efficacy and safety. Description of the state of knowledge: Rhinosinusitis is an inflammation of the mucosa present in the nose and the paranasal sinuses. It affects many patients yearly, bearing significant adverse effects on quality of life, productivity and healthcare expenditure. Acute rhinosinusitis lasts less than 12 weeks and is divided into viral, post-viral and acute bacterial rhinosinusitis. It is one of the prevailing reasons for unfounded antibiotics prescription, although it is usually self-limiting. Its treatment depends on the clinical stage of the infection, however, each of them encloses medications administered intranasally. Based on EPOS2020 and scientific publications it seems that nasal decongestants may be prescribed in viral rhinosinusitis, nasal corticosteroids in post-viral rhinosinusitis and nasal saline can prove beneficial in all clinical stages of rhinosinusitis. While used appropriately all aforementioned medications prove to be safe. Conclusions: In the light of the findings presented in this paper, it can be concluded that acute rhinosinusitis should be treated not only with oral, but also with intranasal drugs. Nasal decongestants are to be considered in viral rhinosinusitis mainly. Nasal corticosteroids show some positive effect in post-viral rhinosinusitis. Nasal saline can be administered in all clinical stages of acute rhinosinusitis. It is crucial to caution the patients against misuse of the medications, in order to prevent their adverse effects.